Effect of Anderson Localization on Auger Destruction of DNA. (5th December 2012) - Turaeva, N. N.; Schroeder, S.; Oksengendler, B. L.
Abstract : The effect of Anderson localization in DNA on the Auger destruction by the Coulombic explosion at ionized radiation has been theoretically discussed in the present work. The theory of Auger destruction of DNA has been modified taking into account the localized and delocalized electron states in DNA owing to the correlated disorder in a sequence of nucleotides. According to the modified theoretical model of Auger destruction, the dominant ratio of delocalized states to localized states in exon compared to intron results in stronger radiation resistance of exons to ionized irradiation causing the Auger-cascade process than the radiation resistance of introns.